2009
DOI: 10.1016/j.bbrc.2009.03.128
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 6 binds calmodulin in a calcium-dependent manner

Abstract: Aquaporin 6 (AQP6) is an anion channel that is expressed primarily in acid secreting α-intercalated cells of the kidney collecting duct. In addition, AQP6 anion channel permeability is gated by low pH. Inspection of the N-terminus of AQP6 revealed a putative calmodulin binding site. AQP6-expressing CHO-K1 cell lysates were mixed with calmodulin beads and AQP6 was pulled down in the presence of calcium. Mutagenesis of the N-terminal calmodulin binding site in full length mouse AQP6 resulted in a loss of calmodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…The overexpression of AQP6 in CNs remains unexplained, as aquaporin 6 (AQP6) is an anion channel expressed primarily in the kidney and in other tissues, such as the cerebellum 21 . The calcium‐dependent binding of AQP6 to calmodulin 22 or its potential role during development 21 may be involved. Slit1 has been shown to play an important role in axonal guidance and dendritic growth of developing neurons 23 and to be related to cancer development, more particularly in neuroblastomas 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of AQP6 in CNs remains unexplained, as aquaporin 6 (AQP6) is an anion channel expressed primarily in the kidney and in other tissues, such as the cerebellum 21 . The calcium‐dependent binding of AQP6 to calmodulin 22 or its potential role during development 21 may be involved. Slit1 has been shown to play an important role in axonal guidance and dendritic growth of developing neurons 23 and to be related to cancer development, more particularly in neuroblastomas 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of calcium in trafficking of vesicles containing AQP5 has been demonstrated in human salivary gland cells in which thapsigargin and calcium ionophores induced AQP5 trafficking (Ishikawa et al, 1998a). A putative calmodulin binding site at the N-terminus of AQP6 has also been identified (Rabaud et al, 2009). Calmodulin binding may have a role in the translocation of AQP6 to the cell surface; it is likely that trafficking of the majority of AQPs are stimulated by calcium elevations (Rabaud et al, 2009).…”
Section: Calciummentioning
confidence: 99%
“…A putative calmodulin binding site at the N-terminus of AQP6 has also been identified (Rabaud et al, 2009). Calmodulin binding may have a role in the translocation of AQP6 to the cell surface; it is likely that trafficking of the majority of AQPs are stimulated by calcium elevations (Rabaud et al, 2009). …”
Section: Calciummentioning
confidence: 99%
See 1 more Smart Citation
“…AQPs have been identified to share sequence homology with calmodulin (Fotiadis et al, 2002) and calmodulin binding sites have been identified within the structure of AQP6 (Rabaud et al, 2009). Ca with an emphasis on the latter regulating AQP trafficking (Benfenati and Ferroni, 2010).…”
Section: Calciummentioning
confidence: 99%